2004
DOI: 10.1002/hep.20364
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study of TIPS versus paracentesis plus albumin in cirrhosis with severe ascites

Abstract: The transjugular intrahepatic portosystemic shunt (TIPS) has been shown to be effective in the control of refractory or recidivant ascites. However, the effect of TIPS on survival as compared with that of large-volume paracentesis plus albumin is uncertain. A multicenter, prospective, clinical trial was performed in 66 patients with cirrhosis and refractory or recidivant ascites (16 Child-Turcotte-Pugh class B and 50 Child-Turcotte-Pugh class C) randomly assigned to treatment with TIPS (n ‫؍‬ 33) or with large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
246
7
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(274 citation statements)
references
References 21 publications
7
246
7
14
Order By: Relevance
“…Survival in the setting of HCC is often limited by the patients' degree of underlying liver dysfunction rather than tumor burden. Patients with indwelling TIPS have already manifested the sequelae of portal hypertension, and median survival in these patients is clearly shorter than those without significant liver dysfunction [28,29]. Therefore, in the setting of TIPS, survival may be more limited by underlying liver disease rather than tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Survival in the setting of HCC is often limited by the patients' degree of underlying liver dysfunction rather than tumor burden. Patients with indwelling TIPS have already manifested the sequelae of portal hypertension, and median survival in these patients is clearly shorter than those without significant liver dysfunction [28,29]. Therefore, in the setting of TIPS, survival may be more limited by underlying liver disease rather than tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of new or worsening HE ranges from 10-44% 3 , and factors associated with post-TIPS HE development include prior history of HE, increasing age, shunt caliber, high creatinine levels, low serum sodium concentration and liver dysfunction 95,115 . Previously, studies with bare metal stents found an increased risk for the development of HE after TIPS insertion for ascites 57,58,59,60,61,62 . Consequently, studies with covered stents found to have lower rates of HE after TIPS placement 113,116 .…”
Section: Portosystemic Shunting Relatedmentioning
confidence: 99%
“…A PPG less than 12 mmHg 3 should be achieved in patients with a history of bleeding esophageal varices and refractory ascites. However the optimal PPG for refractory ascites is still under much debate with some authors suggesting a PPG of less than 8mmHg 59 . In patients with pre-existing HE, a higher gradient may be appropriate to reduce post-TIPS HE 104 , more data is needed to elucidate this.…”
Section: Portal Venous Access and Tips Insertionmentioning
confidence: 99%
“…What could be the source of this disparity? One explanation is a methodological differences between the current study and prior studies [2][3][4]8]. Other studies censored patients who underwent OLT, such that the date of transplantation was considered the last day of follow-up and not counted as an event.…”
mentioning
confidence: 92%
“…
Although a survival benefit following transjugular intrahepatic portosystemic shunt (TIPS) creation for variceal bleeding [1] and ascites [2,3] has been reported in randomized controlled trials (RCTs) in cirrhotic patients, clinical outcomes after TIPS placement in patients with late-stage liver disease and high Model for End-Stage Liver Disease (MELD) scores remain controversial. The MELD score was originally created to predict the survival after TIPS placement in patients with cirrhosis; by intention, a high MELD score predicts poor survival after TIPS [4].
…”
mentioning
confidence: 99%